Transabdominal preperitoneal laparoscopic method for treatment of emergency groin hernias in adult patients - Thanh Xuan Nguyen; Duc Anh Le; Hoai Anh Vu; Thanh Hai Phan; Nhu Hien Pham; Minh Duc Pham; Ngoc Hung Pham (Romanian Medical Journal)
Background. Emergency groin hernia is an understudied research field despite its severity requiring emergency surgery associated with high postoperative morbidity and mortality rates. Therefore, the purpose of this study was to investigate the efficacy, critical technical elements, and management of problems associated with the transabdominal preperitoneal (TAPP) laparoscopic technique for adult patients in need of an emergency groin hernia repair. Methods. We analyzed adult patients who were treated between January 2021 and March 2023 for emergency groin hernia repair. These patients' preoperative data were examined. Results. The surgery was successfully performed on all 21 patients. The duration of the surgery was 71.6±19.7 minutes (range, 45–120 minutes). The hospitalization time was 3.2±2.2 days (range, 2–5 days). Conclusions. The TAPP approach is a secure and efficient method for performing emergency groin hernia repair in adults due to its ability to evaluate hernia content and reduce the incidence of incisional infection.